Association of sugar-sweetened beverage consumption and sleep quality with anxiety symptoms: a cross-sectional study of Tibetan college students at high altitude - Qin Qiu; Guangxin Chai; Shiming Xie; Tianyu Wu (Frontiers in Psychology, 2024)
BackgroundResearch on the association between sugar-sweetened beverages (SSBs) consumption and sleep quality with anxiety symptoms has been highly emphasized. However, past studies have focused on college students in plains areas, while fewer research studies have been conducted on Tibetan college students at high altitudes. Whether this association changes due to ethnicity or altitude is unclear. The present study will contribute to the prevention and intervention of depressive symptoms among Tibetan college students at high altitude.MethodsA self-assessment questionnaire was administered to 3,026 university students (1,491 boys students, 49.27%) on SSBs consumption, sleep quality and anxiety symptoms status in the Tibetan Plateau, a high-altitude region of China. Logistic regression analysis and ordered logistic regression analysis in generalized linear model were used to analyze the association between SSBs consumption and sleep quality with anxiety symptoms.ResultsThe prevalence of anxiety symptoms among Tibetan college students at high altitude was 26.9%. SSBs consumption of ≤1 times/week, 2–5 times/week, and ≥ 6 times/week were 20.7, 28.1, and 45.7%, respectively, with statistically significant differences (χ2 value of 134.353, p < 0.001). Anxiety detection rates for Sleep quality of Good (PSQI ≤5), Moderate (PSQI 6–7), and Poor (PSQI >7) were 16.8, 19.8, and 32.0%, respectively, and the difference was also statistically significant (χ2 value was 73.761, p < 0.001). The ordered logistic regression analysis in the generalized linear model showed that, overall, the group of college students with SSBs ≤1 times/week and sleep quality of Good served as the reference group, and the group with SSBs ≥6 times/week and sleep quality of Poor (OR: 5.06, 95% CI: 3.75–6.83) had the highest risk of anxiety symptoms.ConclusionSSBs consumption and sleep quality were associated with anxiety symptoms, and there was an interaction effect. Effective control of SSBs consumption and improvement of sleep quality may be important factors in preventing and reducing the occurrence of anxiety symptoms.